Exploring the Relationship Between Trait Mindfulness and Interpersonal Sensitivity for Chinese College Students: The Mediating Role of Negative Emotions and Moderating Role of Effectiveness/Authenticity - Ding, Xiaoqian; Zhao, Tian; Li, Xiaoxi; Yang, Zirong; Tang, Yi-Yuan (Frontiers in Psychology, 2021)
Background: Interpersonal sensitivity is a prominent mental health problem facing college students today. Trait mindfulness is a potential positive factor that may influence interpersonal relationships. However, the precise relationship between trait mindfulness and interpersonal sensitivity remains elusive, which limits the optimization and further application of mindfulness-based intervention schemes targeting interpersonal sensitivity. This study aimed to explore (a) whether negative emotions mediate the relationship between trait mindfulness and interpersonal sensitivity, and (b) whether the relationship among trait mindfulness, negative emotions and interpersonal sensitivity are moderated by effectiveness/ authenticity. We hypothesize that (a) negative emotions mediate the relationship between trait mindfulness and interpersonal sensitivity, and (b) effectiveness/ authenticity moderates the indirect association between trait mindfulness and interpersonal sensitivity through negative emotions. Methods: 1419 Chinese college students (1023 females, 396 males) age from 17 to 23 (SD=0.86, mean=18.38) participated in this study. Their trait mindfulness, negative emotions, the effectiveness/ authenticity, and interpersonal sensitivity were measured using well-validated self-report questionnaires. Results: Correlational analyses indicated that both trait mindfulness and effectiveness / authenticity were significantly and negatively associated with interpersonal sensitivity. Mediation analyses uncovered a partial mediating role of negative emotions in the relationship between trait mindfulness and interpersonal sensitivity. Moderated mediation analyses showed that in college students with high effectiveness/ authenticity, the relationship between trait mindfulness and negative emotions was stronger, whereas the relationship between negative emotions and interpersonal sensitivity was weaker. Conclusion: Negative emotion is a mediator of the relationship between trait mindfulness and interpersonal sensitivity, which in turn is moderated by effectiveness/ authenticity. These findings suggest a potential mechanism through which trait mindfulness influences interpersonal sensitivity. Mindfulness-based interventions have the potential to decrease interpersonal sensitivity and offer a basis for predicting individual differences in response to mindfulness-based interventions amongst individuals.